2018
DOI: 10.1002/lpor.201800126
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Power Continuous‐Wave Second Harmonic Generation in Semiconductor Nanowires

Abstract: Semiconductor nanowires (NWs) are promising for realizing various on‐chip nonlinear optical devices, due to their nanoscale lateral confinement and strong light–matter interaction. However, high‐intensity pulsed pump lasers are typically needed to exploit their optical nonlinearity because light couples poorly with nanometric‐size wires. Here, microwatts continuous‐wave light pumped second harmonic generation (SHG) in AlGaAs NWs is demonstrated by integrating them with silicon planar photonic crystal cavities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…For instance, the first NW laser at the telecom-band was realized by integrating an InP NW onto a silicon PPC nanocavity [14] . This geometry also enables a microwatts continuous-wave pumped second harmonic generations in an AlGaAs NW [15] . Comparing to other optical cavities, the transverse confinements of resonant modes in PPC nanocavities are provided by the photonic bandgap of the periodic air-holes, promising the design of nanoscale cavities with high quality (Q) factors [16] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the first NW laser at the telecom-band was realized by integrating an InP NW onto a silicon PPC nanocavity [14] . This geometry also enables a microwatts continuous-wave pumped second harmonic generations in an AlGaAs NW [15] . Comparing to other optical cavities, the transverse confinements of resonant modes in PPC nanocavities are provided by the photonic bandgap of the periodic air-holes, promising the design of nanoscale cavities with high quality (Q) factors [16] .…”
mentioning
confidence: 99%
“…With the developed growth techniques of semiconductor NWs, it is possible to integrate them onto PPC nanocavities via transfer-manipulation process or insitu growth [15,19,20] . Because NWs' cross-sections and PPC nanocavities are both in the nanoscale, their spatial alignments would significantly determine the light-NW coupling strengths.…”
mentioning
confidence: 99%
“…Individual III-V nanoantennas supporting electric and magnetic multipolar resonances [26,[28][29][30][31][32] have already demonstrated ultrahigh efficiency of second-harmonic generation (SHG) in subwavelength structures. [33][34][35] In addition to these advantages, semiconductor nanostructures can also be electrically doped and used for subwavelength active devices. [36,37] The control of the nanoantennas' geometry allows to manipulate the resonances excited in the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging their unique photonic structures, lightmatter interactions and light wave propagations in PPC waveguides or cavities could be controlled effectively in a spatial scale of subwavelength, which is comparable to the thickness of NWs. Recently, a number of works have reported on the integration of NWs with PPC waveguides and nanocavities, which realize significantly enhanced light-NW couplings [18,[20][21][22][23]. For instance, Notomi et al demonstrated the first NW laser at the telecom band by integrating an InP NW into a groove trench of a silicon PPC waveguide, which induced a high-quality (Q) resonant mode [24].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Notomi et al demonstrated the first NW laser at the telecom band by integrating an InP NW into a groove trench of a silicon PPC waveguide, which induced a high-quality (Q) resonant mode [24]. In our previous work, high-efficiency second-harmonic generation (SHG) was achieved in an AlGaAs NW integrated on a PPC nanocavity, which could be pumped even by a continuous-wave (CW) laser with submicrowatt power [22].…”
Section: Introductionmentioning
confidence: 99%